The Use of AIH Techniques for the Literacy Development of Grade 5 Students at Sukarasa State Elementary School - Evi Maylitha; Muh Husen Arifin (CV. Rayyan Dwi Bharata, 2023)
The School Literacy Movement is a literacy movement in educational institutions such as schools whose activities emphasize the activity of reading information by students to gain knowledge. In fact, literacy activities are still seen as reading activities only. So that literacy is still less attractive to students. One of the contributing factors is the monotonous strategy used. Many techniques can be used in reading and writing literacy activities. One of the literacy activity techniques used by grade 5 at SDN Sukarasa is the AIH (Reason, Content, and Wisdom) technique. Literacy activities with this technique are carried out by writing a review regarding the reasons for choosing reading material, the contents of the reading, and the lessons from the reading. This study aims to determine the use of AIH techniques on students' literacy development. The methods used in this research are interviews and documentation. The results showed that literacy activities using the AIH technique improved students' reading skills, but not their writing abilities.